Some Fixed Point Theorems in C-complete Complex Valued Metric Spaces - Dubey, Anil Kumar; Bibay, Shweta; Dubey, R. P.; Pandey, M. D. (Communications in Mathematics and Applications, 2018)
In this paper, we prove common fixed point theorems for a pair of mappings satisfying rational inequality in C-complete complex valued metric spaces. The results of this paper generalize and extend the known results in C-complete complex valued metric spaces.